The role of sulfonate groups and hydrogen bonding in the proton conductivity of two coordination networks - Javed, Ali; Steinke, Felix; Wöhlbrandt, Stephan; Bunzen, Hana; Stock, Norbert; Tiemann, Michael (Beilstein Journal of Nanotechnology)
The proton conductivity of two coordination networks, [Mg(H 2 O) 2 (H 3 L)]·H 2 O and [Pb 2 (HL)]·H 2 O (H 5 L = (H 2 O 3 PCH 2 ) 2 -NCH 2 -C 6 H 4 -SO 3 H), is investigated by AC impedance spectroscopy. Both materials contain the same phosphonato-sulfonate linker molecule, but have clearly different crystal structures, which has a strong effect on proton conductivity. In the Mg-based coordination network, dangling sulfonate groups are part of an extended hydrogen bonding network, facilitating a “proton hopping” with low activation energy; the material shows a moderate proton conductivity. In the Pb-based metal-organic framework, in contrast, no extended hydrogen bonding occurs, as the sulfonate groups coordinate to Pb 2+ , without forming hydrogen bonds; the proton conductivity is much lower in this material.
Keywords: Electrical and Electronic Engineering; General Physics and Astronomy; General Materials Science

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos, Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas; Grundmeier, Guido (Applied Surface Science)
Near ambient pressure XPS in nitrogen atmosphere was utilized to investigate gas-solid interactions within porous SiO2 films ranging from 30 to 75 nm thickness. The films were differentiated in terms of porosity and roughness. The XPS N1s core levels of the N2 gas in presence of the SiO2 samples showed variations in width, binding energy and line shape. The width correlated with the surface charge induced in the dielectric films upon X-ray irradiation. The observed different binding energies observed for the N1s peak can only partly be associated with intrinsic work function differences between the samples, opening the possibility that the effect of physisorption at room temperature could be detected by a shift in the measured binding energy. However, the signals also show an increasing asymmetry with rising surface charge. This might be associated with the formation of vertical electrical gradients within the dielectric porous thin films, which complicates the assignment of binding energy positions to specific surface-related effects. With the support of Monte Carlo and first principles density functional theory calculations, the observed shifts were discussed in terms of the possible formation of transitory dipoles upon N2 physisorption within the porous SiO2 films.
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

The Structure of Water in Silica Mesopores – Influence of the Pore Wall Polarity - Weinberger, Christian; Zysk, Frederik; Hartmann, Marc; Kaliannan, Naveen; Keil, Waldemar; Kühne, Thomas; Tiemann, Michael (Advanced Materials Interfaces)
In the spatial confinement of cylindrical mesopores with diameters of a few nanometers, water molecules experience restrictions in hydrogen bonding. This leads to a different behavior regarding the molecular orientational freedom (‘structure of water') compared to the bulk liquid state. In addition to the pore size, the behavior is also strongly affected by the strength of the pore wall-to-water interactions, that is, the pore wall polarity. In this work, this is studied both experimentally and theoretically. The surface polarity of mesoporous silica (SiO2) is modified by functionalization with trimethylsilyl moieties, resulting in a change from a hydrophilic (pristine) to a hydrophobic pore wall. The mesopore surface is characterized by N2 and H2O sorption experiments. Those results are combined with IR spectroscopy to investigate pore wall-to-water interactions leading to different structures of water in the mesopore. Furthermore, the water's structure is studied theoretically to gain deeper insight into the interfacial interactions. For this purpose, the structure of water is analyzed by pairing densities, coordination, and angular distributions with a novel adaptation of surface-specific sum-frequency generation calculation for pore environments.
Keywords: Mechanical Engineering; Mechanics of Materials

Pyrolysis of sucrose-derived hydrochar - Wortmann, Martin; Keil, Waldemar; Brockhagen, Bennet; Biedinger, Jan; Westphal, Michael; Weinberger, Christian; Diestelhorst, Elise; Hachmann, Wiebke; Zhao, Yanjing; Tiemann, Michael; Reiss, Günter; Hüsgen, Bruno; et al. (Journal of Analytical and Applied Pyrolysis)
The electrochemical properties of carbonaceous materials produced by hydrothermal carbonization, referred to as hydrochar, can be substantially improved by post-carbonization via pyrolysis. Although these materials have been widely studied for a variety of applications, the mechanisms underlying the pyrolysis are yet poorly understood. This study provides a comprehensive temperature-resolved characterization of the chemical composition, morphology and crystallinity of sucrose-derived hydrochar during pyrolysis. Thermogravimetric analysis, differential scanning calorimetry, and elemental analysis have shown that the dry hydrochar loses about 41% of its dry mass due to the exothermic disintegration of oxygen-containing groups until the carbonization is completed at about 850 °C with a total carbon yield of 93%. The carbonization and aromatization of the initially furanic and keto-aliphatic structure were analyzed by 13C solid-state nuclear magnetic resonance spectroscopy, X-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy. The transition from an amorphous to a nanocrystalline graphitic structure was analyzed using X-ray diffraction and Raman spectroscopy. The pore formation mechanism was examined by helium ion microscopy, transmission electron microscopy, and nitrogen adsorption measurements. The results indicate the formation of oxygen-rich nanoclusters up to 700 °C, which decompose up to 750 °C leaving behind equally sized pores, resulting in a surface area of up to 480 m2/g.
Keywords: Analytical Chemistry; Fuel Technology

Porous SiO2 coated dielectric metasurface with consistent performance independent of environmental conditions - Geromel, René; Weinberger, Christian; Brormann, Katja; Tiemann, Michael; Zentgraf, Thomas (Optical Materials Express)
With the rapid advances of functional dielectric metasurfaces and their integration on on-chip nanophotonic devices, the necessity of metasurfaces working in different environments, especially in biological applications, arose. However, the metasurfaces’ performance is tied to the unit cell’s efficiency and ultimately the surrounding environment it was designed for, thus reducing its applicability if exposed to altering refractive index media. Here, we report a method to increase a metasurface’s versatility by covering the high-index metasurface with a low index porous SiO2 film, protecting the metasurface from environmental changes while keeping the working efficiency unchanged. We show, that a covered metasurface retains its functionality even when exposed to fluidic environments.

Development of Battery System Based on Na-S and Characterization Using X-ray Absorption Spectroscopy - Tonbul, Güldeniz; Kappler, Julian; Murugan, Saravanakumar; Schoch, Roland; Nowakowski, Michal; Lange, Pia; Bauer, Matthias; Buchmeiser, Michael R.

Quality or Quantity? How Structural Parameters Affect Catalytic Activity of Iron Oxides for CO Oxidation - Schlicher, Steffen; Prinz, Nils; Bürger, Julius; Omlor, Andreas; Singer, Christian; Zobel, Mirijam; Schoch, Roland; Lindner, Jörg K. N.; Schünemann, Volker; Kureti, Sven; Bauer, Matthias (Catalysts)
<The replacement of noble metal catalysts by abundant iron as an active compound in CO oxidation is of ecologic and economic interest. However, improvement of their catalytic performance to the same level as state-of-the-art noble metal catalysts requires an in depth understanding of their working principle on an atomic level. As a contribution to this aim, a series of iron oxide catalysts with varying Fe loadings from 1 to 20 wt% immobilized on a γ-Al2O3 support is presented here, and a multidimensional structure–activity correlation is established. The CO oxidation activity is correlated to structural details obtained by various spectroscopic, diffraction, and microscopic methods, such as PXRD, PDF analysis, DRUVS, Mössbauer spectroscopy, STEM-EDX, and XAS. Low Fe loadings lead to less agglomerated but high percentual amounts of isolated, tetrahedrally coordinated iron oxide species, while the absolute amount of isolated species reaches its maximum at high Fe loadings. Consequently, the highest CO oxidation activity in terms of turnover frequencies can be correlated to small, finely dispersed iron oxide species with a large amount of tetrahedrally oxygen coordinated iron sites, while the overall amount of isolated iron oxide species correlates with a lower light-off temperature.
Keywords: Physical and Theoretical Chemistry; Catalysis; General Environmental Science; Key

High resolution off resonant spectroscopy as a probe of the oxidation state - Nowakowski, Michał; Kalinko, Aleksandr; Szlachetko, Jakub; Fanselow, Rafał; Bauer, Matthias (Journal of Analytical Atomic Spectrometry)
Currently, chemistry and physics are strongly dependent on the concept of the oxidation state. While the formal oxidation state is easily evaluated, the real physical oxidation state value is often difficult to determine and significantly varies from the formal values. Determination of the ionization threshold in X-ray absorption spectroscopy (XANES) relies on the absorption edge position and sometimes poses limitations, mainly due to the edge resonances. Moreover, the lower energy states can be probed only within x-soft or XUV photons providing only surface state information of probed materials. Here, we employ high energy resolution off-resonant spectroscopy to determine both 1s and 3p binding energies of Fe-based materials and therefore correlate to their physical oxidation state. The results are compared to the ones obtained with classical X-ray absorption, X-ray emission, and photoelectron spectroscopies. The observed differences in binding energies are discussed in a frame of initial and final state interactions with the atom's electronic configurations. The presented methodology is discussed towards potential use to single-shot experiments and application at X-ray free-electron lasers. Alternatively, core level X-ray emission spectroscopy can be used, but the emission line positions are strongly affected by spin-orbit interaction. However, due to the energy transfer from the photon to the excited core electron, the same information as in XANES is probed in high energy resolution off-resonant spectroscopy (HEROS). Based on the Kramers–Heisenberg theory, we propose a new approach for ionization threshold determination which is free of the limitations encountered in XANES-based determination of the core state energy. Namely, the value of core state energy can be determined analytically using a few HEROS spectra recorded with significantly higher spectral resolution. This approach provides a basis for the universal physical oxidation state determination method.
Keywords: Spectroscopy; Analytical Chemistry

Digitization in Catalysis Research: Towards a Holistic Description of a Ni/Al2O3 Reference Catalyst for CO2 Methanation - Weber, Sebastian; Zimmermann, Ronny T.; Bremer, Jens; Abel, Ken L.; Poppitz, David; Prinz, Nils; Ilsemann, Jan; Wendholt, Sven; Yang, Qingxin; Pashminehazar, Reihaneh; Monaco, Federico; Cloetens, Peter; et al. (ChemCatChem)
Increasing the metal-to-ligand charge transfer (MLCT) excited state lifetime of polypyridine iron(II) complexes can be achieved by lowering the ligand's π* orbital energy and by increasing the ligand field splitting. In the homo- and heteroleptic complexes [Fe(cpmp)2]2+ (12+) and [Fe(cpmp)(ddpd)]2+ (22+) with the tridentate ligands 6,2’’-carboxypyridyl-2,2’-methylamine-pyridyl-pyridine (cpmp) and N,N’-dimethyl-N,N’-di-pyridin-2-ylpyridine-2,6-diamine (ddpd) two or one dipyridyl ketone moieties provide low energy π* acceptor orbitals. A good metal-ligand orbital overlap to increase the ligand field splitting is achieved by optimizing the octahedricity through CO and NMe units between the coordinating pyridines which enable the formation of six-membered chelate rings. The push-pull ligand cpmp provides intra-ligand and ligand-to-ligand charge transfer (ILCT, LL'CT) excited states in addition to MLCT excited states. Ground and excited state properties of 12+ and 22+ were accessed by X-ray diffraction analyses, resonance Raman spectroscopy, (spectro)electrochemistry, EPR spectroscopy, X-ray emission spectroscopy, static and time-resolved IR and UV/Vis/NIR absorption spectroscopy as well as quantum chemical calculations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Stimulation and Enhancement of Near‐Band‐Edge Emission in Zinc Oxide by Distributed Bragg Reflectors - Kothe, Linda; Albert, Maximilian; Meier, Cedrik; Wagner, Thorsten; Tiemann, Michael (Advanced Materials Interfaces)
The free exciton transition (near-band-edge emission, NBE) of ZnO at ≈388 nm can be strongly enhanced and even stimulated by an underlying photonic structure. 1D Photonic crystals, so-called distributed Bragg reflectors, are utilized to suppress the deep-level emission of ZnO (DLE, ≈500–530 nm). The reflector stacks are fabricated in a layer-by-layer procedure by wet-chemical synthesis. They consist of low-ε porous SiO2 layers and high-ε TiO2 layers. Varying the thickness of the SiO2 layers allows tuning the optical bandgap in a wide range between ≈420 and 800 nm. A ZnO layer is deposited on top of the reflector stacks by sol–gel synthesis. The spontaneous photoluminescence (PL) emission of the ZnO film is modulated by the photonic structure. When the optical bandgap of the reflector is in resonance with the deep-level emission of ZnO (DLE, ≈500–530 nm), then this defect-related emission mode is suppressed. Strong NBE emission is observed even when the ZnO layer does not show any NBE emission (due to low crystallinity) in the absence of the photonic structure. With this cost-efficient synthesis method, emitters for, e.g., luminescent gas sensors can be fabricated.
Keywords: Mechanical Engineering; Mechanics of Materials

Iron oxide catalysts for CO oxidation : from basic structure-activity-correlation to an advanced preparation strategy for highly active catalysts - Schlicher, Steffen

Probing the Interactions of Immobilized Ruthenium Dihydride Complexes with Metal Oxide Surfaces by MAS NMR: Effects on CO2 Hydrogenation - Nguyen, Hoang-Huy; Li, Zheng; Enenkel, Toni; Hildebrand, Joachim; Bauer, Matthias; Dyballa, Michael; Estes, Deven P. (The Journal of Physical Chemistry C)
Homogeneous catalysts immobilized on metal oxides often have different catalytic properties than in homogeneous solution. This can be either activating or deactivating and is often attributed to interactions of catalyst species with the metal oxide surface. However, few studies have ever demonstrated the effect that close associations of active sites with surfaces have on the catalytic activity. In this paper, we immobilize H2Ru(PPh3)2(Ph2P)2N–C3H6–Si(OEt)3 (3) on SiO2, Al2O3, and ZnO and interrogate the relationship to the surface using IR, MAS NMR, 1H–31P HETCOR, and XAS spectroscopies. We found that while there are close contacts between the P atoms of the complex and all three metal oxide surfaces, the Ru–H bond only reacts with oxygen bridges on SiO2 and Al2O3, forming new Ru–O bonds. In contrast, complex 3 stays intact on ZnO. Comparison of the catalytic activities of our immobilized species for CO2 hydrogenation to ethyl formate showed that Lewis acidic metal oxides activate, rather than deactivate, complex 3 in the order Al2O3 > ZnO > SiO2. The Lewis acidic sites on the metal oxide surfaces most likely increase the productivity by increasing the rate of esterification of formate intermediates.
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Olefin Metathesis in Confinement: Towards Covalent Organic Framework Scaffolds for Increased Macrocyclization Selectivity - Emmerling, Sebastian T.; Ziegler, Felix; Fischer, Felix R.; Schoch, Roland; Bauer, Matthias; Plietker, Bernd; Buchmeiser, Michael R.; Lotsch, Bettina V. (Chemistry – A European Journal)
Covalent organic frameworks (COFs) offer vast structural and chemical diversity enabling a wide and growing range of applications. While COFs are well-established as heterogeneous catalysts, so far, their high and ordered porosity has scarcely been utilized to its full potential when it comes to spatially confined reactions in COF pores to alter the outcome of reactions. Here, we present a highly porous and crystalline, large-pore COF as catalytic support in α,ω-diene ring-closing metathesis reactions, leading to increased macrocyclization selectivity. COF pore-wall modification by immobilization of a Grubbs-Hoveyda-type catalyst via a mild silylation reaction provides a molecularly precise heterogeneous olefin metathesis catalyst. An increased macro(mono)cyclization (MMC) selectivity over oligomerization (O) for the heterogeneous COF-catalyst (MMC:O=1.35) of up to 51 % compared to the homogeneous catalyst (MMC:O=0.90) was observed along with a substrate-size dependency in selectivity, pointing to diffusion limitations induced by the pore confinement.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Higher MLCT lifetime of carbene iron(ii) complexes by chelate ring expansion - Reuter, Thomas; Kruse, Ayla; Schoch, Roland; Lochbrunner, Stefan; Bauer, Matthias; Heinze, Katja (Chemical Communications)
Combining strong σ-donating N-heterocyclic carbene ligands and π-accepting pyridine ligands with a high octahedricity in rigid iron(II) complexes increases the 3MLCT lifetime from 0.15 ps in the prototypical [Fe(tpy)2]2+ complex to 9.2 ps in [Fe(dpmi)2]2+12+. The tripodal CNN ligand dpmi (di(pyridine-2-yl)(3-methylimidazol-2-yl)methane) forms six-membered chelate rings with the iron(II) centre leading to close to 90° bite angles and enhanced iron-ligand orbital overlap
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Photoactive iron complexes: more sustainable, but still a challenge - Dierks, Philipp; Vukadinovic, Yannik; Bauer, Matthias (Inorganic Chemistry Frontiers)
On transition metals such as iron rests lots of hope to replace precious metal catalysts in the field of photochemistry for a more sustainable future. Indeed, significant progress has been made in recent years in terms of lifetime extension and emerging applications in catalysis. For this reason, recent synthetic strategies of new photoactive iron compounds, which have proved to show particularly promising properties, are reviewed here. The lifetime of the excited state serves as a key parameter for comparison with the standard ruthenium complex, [Ru(bpy)3]2+, to discuss the potential and performance of the iron complexes. This approach is complemented by a more holistic examination of the sustainability of such a substitution strategy in order to answer the question: when or at which point can we assume that iron represents a more sustainable alternative for noble metals in photochemical applications?
Keywords: Inorganic Chemistry

Selective Benzylic CH‐Borylations by Tandem Cobalt Catalysis - Ghosh, Pradip; Schoch, Roland; Bauer, Matthias; Jacobi von Wangelin, Axel (Angewandte Chemie International Edition)
Metal-catalyzed C−H activations are environmentally and economically attractive synthetic strategies for the construction of functional molecules as they obviate the need for pre-functionalized substrates and minimize waste generation. Great challenges reside in the control of selectivities, the utilization of unbiased hydrocarbons, and the operation of atom-economical dehydrocoupling mechanisms. An especially mild borylation of benzylic CH bonds was developed with the ligand-free pre-catalyst Co[N(SiMe3)2]2 and the bench-stable and inexpensive borylation reagent B2pin2 that produces H2 as the only by-product. A full set of kinetic, spectroscopic, and preparative mechanistic studies are indicative of a tandem catalysis mechanism of CH-borylation and dehydrocoupling via molecular CoI catalysts.
Keywords: General Chemistry; Catalysis

Electrochemical Reduction and Oxidation of Ruddlesden–Popper-Type La2NiO3F2 within Fluoride-Ion Batteries - Wissel, Kerstin; Schoch, Roland; Vogel, Tobias; Donzelli, Manuel; Matveeva, Galina; Kolb, Ute; Bauer, Matthias; Slater, Peter R.; Clemens, Oliver (Chemistry of Materials)
Within this article, it is shown that an electrochemical defluorination and additional fluorination of Ruddlesden–Popper-type La2NiO3F2 is possible within all-solid-state fluoride-ion batteries. Structural changes within the reduced and oxidized phases have been examined by X-ray diffraction studies at different states of charging and discharging. The synthesis of the oxidized phase La2NiO3F2+x proved to be successful by structural analysis using both X-ray powder diffraction and automated electron diffraction tomography techniques. The structural reversibility on re-fluorinating and re-defluorinating is also demonstrated. Moreover, the influence of different sequences of consecutive reduction and oxidation steps on the formed phases has been investigated. The observed structural changes have been compared to changes in phases obtained via other topochemical modification approaches such as hydride-based reduction and oxidative fluorination using F2 gas, highlighting the potential of such electrochemical reactions as alternative synthesis routes. Furthermore, the electrochemical routes represent safe and controllable synthesis approaches for novel phases, which cannot be synthesized via other topochemical methods. Additionally, side reactions, occurring alongside the desired electrochemical reactions, have been addressed and the cycling performance has been studied.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

η 3 ‐Coordination and Functionalization of the 2‐Phosphaethynthiolate Anion at Lanthanum(III)** - Watt, Fabian A.; Burkhardt, Lukas; Schoch, Roland; Mitzinger, Stefan; Bauer, Matthias; Weigend, Florian; Goicoechea, Jose M.; Tambornino, Frank; Hohloch, Stephan (Angewandte Chemie International Edition)
We present the η3-coordination of the 2-phosphaethynthiolate anion in the complex (PN)2La(SCP) (2) [PN=N-(2-(diisopropylphosphanyl)-4-methylphenyl)-2,4,6-trimethylanilide)]. Structural comparison with dinuclear thiocyanate-bridged (PN)2La(μ-1,3-SCN)2La(PN)2 (3) and azide-bridged (PN)2La(μ-1,3-N3)2La(PN)2 (4) complexes indicates that the [SCP]− coordination mode is mainly governed by electronic, rather than steric factors. Quantum mechanical investigations reveal large contributions of the antibonding π*-orbital of the [SCP]− ligand to the LUMO of complex 2, rendering it the ideal precursor for the first functionalization of the [SCP]− anion. Complex 2 was therefore reacted with CAACs which induced a selective rearrangement of the [SCP]− ligand to form the first CAAC stabilized group 15–group 16 fulminate-type complexes (PN)2La{SPC(RCAAC)} (5 a,b, R=Ad, Me). A detailed reaction mechanism for the SCP-to-SPC isomerization is proposed based on DFT calculations.
Keywords: General Chemistry; Catalysis

Electronic Structure of a Diiron Complex: A Multitechnique Experimental Study of [(dppf)Fe(CO) 3]+/0 - Winkler, Mario; Schnierle, Marc; Ehrlich, Felix; Mehnert, Kim-Isabelle; Hunger, David; Sheveleva, Alena M.; Burkhardt, Lukas; Bauer, Matthias; Tuna, Floriana; Ringenberg, Mark R.; van Slageren, Joris (Inorganic Chemistry)
Here we explore the electronic structure of the diiron complex [(dppf)Fe(CO)3]0/+ [10/+; dppf = 1,1′-bis(diphenylphosphino)ferrocene] in two oxidation states by an advanced multitechnique experimental approach. A combination of magnetic circular dichroism, X-ray absorption and emission, high-frequency electron paramagnetic resonance (EPR), and Mössbauer spectroscopies is used to establish that oxidation of 10 occurs on the carbonyl iron ion, resulting in a low-spin iron(I) ion. It is shown that an unequivocal result is obtained by combining several methods. Compound 1+ displays slow spin dynamics, which is used here to study its geometric structure by means of pulsed EPR methods. Surprisingly, these data show an association of the tetrakis[3,5-bis(trifluoromethylphenyl)]borate counterion with 1+.
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Planar Iron Hydride Nanoclusters: Combined Spectroscopic and Theoretical Insights into Structures and Building Principles - Chakraborty, Uttam; Bügel, Patrick; Fritsch, Lorena; Weigend, Florian; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemistryOpen)
The controlled assembly of well-defined planar nanoclusters from molecular precursors is synthetically challenging and often plagued by the predominant formation of 3D-structures and nanoparticles. Herein, we report planar iron hydride nanoclusters from reactions of main group element hydrides with iron(II) bis(hexamethyldisilazide). The structures and properties of isolated Fe4, Fe6, and Fe7 nanoplatelets and calculated intermediates enable an unprecedented insight into the underlying building principle and growth mechanism of iron clusters, metal monolayers, and nanoparticles.
Keywords: General Chemistry

Modeling of gyroidal mesoporous CMK-8 and CMK-9 carbon nanostructures and their X-Ray diffraction patterns - Schwind, Bertram; Smått, Jan-Henrik; Tiemann, Michael; Weinberger, Christian (Microporous and Mesoporous Materials)
Powder X-ray diffraction (XRD) patterns of ordered mesoporous CMK-8 and CMK-9 carbon materials are simulated by geometric modeling. The materials are amorphous at the atomic length scale but exhibit highly symmetric gyroidal structures at the nanometer scale, corresponding to regular, continuous nanopore systems with cubic symmetry. Their structures lead to characteristic low-angle XRD signatures. We introduce a model based on geometrical considerations to simulate CMK-8 and CMK-9 structures with variable volume fraction of carbon (vs. pore volume, i.e., variable 'pore wall thickness'). In addition, we also simulate carbon materials with variable amounts of guest species (e.g., sulfur) residing in their pores. The corresponding XRD patterns are calculated. The carbon volume fraction turns out to have a significant impact on the relative diffraction peak intensities, especially in case of CMK-9 carbon that features a bimodal porosity. Likewise, the presence of guest species in the pores may also strongly affect the relative peak intensities. Our study suggests that careful evaluation of experimental low-angle XRD patterns of (real) CMK-8 or CMK-9 materials offers an opportunity to obtain detailed information about the nanostructural properties in addition to the mere identification of the pore systems geometry.

Review of infrared spectroscopy techniques for the determination of internal structure in thin SiO2 films - de los Arcos, Teresa; Müller, Hendrik; Wang, Fuzeng; Damerla, Varun Raj; Hoppe, Christian; Weinberger, Christian; Tiemann, Michael; Grundmeier, Guido (Vibrational Spectroscopy)
A comparison of infrared spectroscopic analytical approaches was made in order to assess their applicability for internal structure characterization of SiO2 thin films. Markers for porosity and/or disorder based on the analysis of the asymmetric stretching absorption band of SiO2 between 900−1350 cm−1 were discussed. The shape of this band, which shows a well-defined LO–TO splitting, depends not only on the inherent characteristics of the film under analysis but also on the particular geometry of the IR experiment and the specific surface selection rules of the substrate. Three types of SiO2 thin films with clearly defined porosity ranging from dense films to mesoporous films were investigated by transmission (at different incidence angles), direct specular reflection (at different angles), and diffuse reflection. Two different types of substrate, metallic and semiconducting, were used. The combined effect of substrate and specific technique in the final shape of the band, was discussed, and the efficacy for their applicability to the determination of porosity in thin SiO2 films was critically evaluated.

Selective Modification of Hierarchical Pores and Surfaces in Nanoporous Materials - Tiemann, Michael; Weinberger, Christian (Advanced Materials Interfaces)
Tailor-made ordered mesoporous materials bear great potential in numerous fields of application where large interfaces are required. However, the inherent surfacechemical properties of conventional materials, such as silica, carbon or organosilica, poses some limitations with respect to their application. Surface manipulation by functionalization with chemically more reactive groups is one way to improve materials for their desired purpose. Another approach is the design of high surface-area composite materials. The surface manipulation, either by functionalization or by introducing guest species, can be performed selectively. This means that when several distinct, i.e. , hierarchical, types of surfaces or pore systems exist in a material, each of them may be chosen for manipulation. Several strategies can be identified to achieve this goal. Molecules or molecule assemblies can be utilized to temporarily protect pores or surfaces (soft protection), while manipulation occurs at the accessible sites. This approach is a recurring motive in this review and can also be applied to rigid template matrices (hard protection). Furthermore, the size of functionalization agents (size protection) and their reactivity/diffusion (kinetic protection) into the pores can also be utilized to achieve selectivity. In addition, challenges in the synthesis and characterization of selectively manipulated ordered mesoporous materials are discussed.

Examination of the evolution of iron oxide nanoparticles in flame spray pyrolysis by tailored in situ particle sampling techniques - Tischendorf, R.; Simmler, M.; Weinberger, Christian; Bieber, M.; Reddemann, M.; Fröde, F.; Lindner, J.; Pitsch, H.; Kneer, R.; Tiemann, Michael; Nirschl, H.; Schmid, H.-J. (Journal of Aerosol Science)
In this report, a flame spray pyrolysis setup has been examined with various in situ extraction methods of particle samples along the flame axis. First, two precursor formulations leading to the formation of iron oxide nanoparticles were used in a standardized SpraySyn burner system, and the final particle outcome was characterized by a broad range of established powder characterization techniques (TEM/HRTEM, SAXS, XRD, BET). The characterization of the powder products evidenced that mostly homogeneous gas-to-particle conversion takes place when applying an acidic precursor solution, whereas the absence of the acid leads to a dominant droplet-to-particle pathway. Our study indicates that a droplet-to-particle-pathway could be present even when processing the acidic formulation. However, even if a secondary pathway might take place in this case as well, it is not dominant and nearly negligible. Subsequently, the in situ particle structure evolution was investigated for the dominant gas-to-particle pathway, and particles were extracted along the flame axis for online SMPS and offline TEM/HRTEM analysis. Due to the highly reactive conditions within the flame (high temperatures, turbulent flow field, high particle number concentrations), the extraction of representative samples from spray flames is challenging. In order to handle the reactive conditions, two extraction techniques were tailored in this report. To extract an aerosol sample within the flame for SMPS measurement, a Hole in a Tube probe was adjusted. Thus, the mobility particle diameter as well as the corresponding distribution widths were obtained at different heights above the burner along the flame axis. For TEM/HRTEM image analysis, particle samples were collected thermophoretically by means of a tailored shutter system. Since all sampling grids were protected until reaching the flame axis and due to the low sampling time, momentary captures of local particle structures could be extracted precisely. The particle morphologies have clearly shown an evolution from spherical and paired particles in the flame center to fractal and compact agglomerates at later synthesis stages.

TiO2 nanoparticle coatings on glass surfaces for the selective trapping of leukemia cells from peripheral blood - Garcia Diosa, Jaime Andres; Gonzalez Orive, Alejandro; Weinberger, Christian; Schwiderek, Sabrina; Knust, Steffen; Tiemann, Michael; Grundmeier, Guido; Keller, Adrian; Camargo Amado, Ruben Jesus (Journal of Biomedical Materials Research Part B: Applied Biomaterials)
Photodynamic therapy (PDT) using TiO2 nanoparticles has become an important alternative treatment for different types of cancer due to their high photocatalytic activity and high absorption of UV-A light. To potentiate this treatment, we have coated commercial glass plates with TiO2 nanoparticles prepared by the sol–gel method (TiO2-m), which exhibit a remarkable selectivity for the irreversible trapping of cancer cells. The physicochemical properties of the deposited TiO2-m nanoparticle coatings have been characterized by a number of complementary surface-analytical techniques and their interaction with leukemia and healthy blood cells were investigated. Scanning electron and atomic force microscopy verify the formation of a compact layer of TiO2-m nanoparticles. The particles are predominantly in the anatase phase and have hydroxyl-terminated surfaces as revealed by Raman, X-ray photoelectron, and infrared spectroscopy, as well as X-ray diffraction. We find that lymphoblastic leukemia cells adhere to the TiO2-m coating and undergo amoeboid-like migration, whereas lymphocytic cells show distinctly weaker interactions with the coating. This evidences the potential of this nanomaterial coating to selectively trap cancer cells and renders it a promising candidate for the development of future prototypes of PDT devices for the treatment of leukemia and other types of cancers with non-adherent cells.

New isoreticular phosphonate MOFs based on a tetratopic linker - Steinke, Felix; Javed, Ali; Wöhlbrandt, Stephan; Tiemann, Michael; Stock, Norbert (Dalton Transactions)
The tetratopic linker 1,1,2,2-tetrakis(4-phosphonophenyl)ethylene (H8TPPE) was used to synthesize the three new porous metal–organic frameworks of composition [M2(H2O)2(H2TPPE)]·xH2O (M = Al3+, Ga3+, Fe3+), denoted as M-CAU-53 under hydrothermal reaction conditions, using the corresponding metal nitrates as starting materials. The crystal structures of the compounds were determined ab initio from powder X-ray diffraction data, revealing small structural differences. Proton conductivity measurements were carried out, indicating different conductivity mechanisms. The differences in proton conductivity could be linked to the individual structures. In addition, a thorough characterization via thermogravimetry, elemental analysis, IR-spectroscopy as well as N2- and H2O-sorption is given.

Distinct photodynamics of κ-N and κ-C pseudoisomeric iron(ii) complexes - Dierks, Philipp; Kruse, Ayla; Bokareva, Olga S.; Al-Marri, Mohammed J.; Kalmbach, Jens; Baltrun, Marc; Neuba, Adam; Schoch, Roland; Hohloch, Stephan; Heinze, Katja; Seitz, Michael; Kühn, Oliver; et al. (Chemical Communications)
Two closely related FeII complexes with 2,6-bis(1-ethyl-1H-1,2,3-triazol-4yl)pyridine and 2,6-bis(1,2,3-triazol-5-ylidene)pyridine ligands are presented to gain new insights into the photophysics of bis(tridentate) iron(II) complexes. The [Fe(N^N^N)2]2+ pseudoisomer sensitizes singlet oxygen through a MC state with nanosecond lifetime after MLCT excitation, while the bis(tridentate) [Fe(C^N^C)2]2+ pseudoisomer possesses a similar 3MLCT lifetime as the tris(bidentate) [Fe(C^C)2(N^N)]2+ complexes with four mesoionic carbenes.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composite; Metallkomplexe; Optical and Magnetic Materials; Catalysis

Confinement Effects for Efficient Macrocyclization Reactions with Supported Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes - Ziegler, Felix; Kraus, Hamzeh; Benedikter, Mathis J.; Wang, Dongren; Bruckner, Johanna R.; Nowakowski, Michał; Weißer, Kilian; Solodenko, Helena; Schmitz, Guido; Bauer, Matthias; Hansen, Niels; Buchmeiser, Michael R. (ACS Catalysis)
For entropic reasons, the synthesis of macrocycles via olefin ring-closing metathesis (RCM) is impeded by competing acyclic diene metathesis (ADMET) oligomerization. With cationic molybdenum imido alkylidene N-heterocyclic carbene (NHC) complexes confined in tailored ordered mesoporous silica, RCM can be run with macrocyclization selectivities up to 98% and high substrate concentrations up to 0.1 M. Molecular dynamics simulations show that the high conversions are a direct result of the proximity between the surface-bound catalyst, proven by extended X-ray absorption spectroscopy, and the surface-located substrates. Back-diffusion of the macrocycles decreases with decreasing pore diameter of the silica and is responsible for the high macrocyclization efficiency. Also, Z-selectivity increases with decreasing pore diameter and increasing Tolman electronic parameter of the NHC. Running reactions at different concentrations allows for identifying the optimum substrate concentration for each material and substrate combination.
Keywords: Catalysis; General Chemistry

Rh(I)/(III)‐N‐Heterocyclic Carbene Complexes: Effect of Steric Confinement Upon Immobilization on Regio‐ and Stereoselectivity in the Hydrosilylation of Alkynes - Panyam, Pradeep K. R.; Atwi, Boshra; Ziegler, Felix; Frey, Wolfgang; Nowakowski, Michał; Bauer, Matthias; Buchmeiser, Michael R. (Chemistry – A European Journal)
Rh(I) NHC and Rh(III) Cp* NHC complexes (Cp*=pentamethylcyclopentadienyl, NHC=N-heterocyclic carbene=pyrid-2-ylimidazol-2-ylidene (Py−Im), thiophen-2-ylimidazol-2-ylidene) are presented. Selected catalysts were selectively immobilized inside the mesopores of SBA-15 with average pore diameters of 5.0 and 6.2 nm. Together with their homogenous progenitors, the immobilized catalysts were used in the hydrosilylation of terminal alkynes. For aromatic alkynes, both the neutral and cationic Rh(I) complexes showed excellent reactivity with exclusive formation of the β(E)-isomer. For aliphatic alkynes, however, selectivity of the Rh(I) complexes was low. By contrast, the neutral and cationic Rh(III) Cp* NHC complexes proved to be highly regio- and stereoselective catalysts, allowing for the formation of the thermodynamically less stable β-(Z)-vinylsilane isomers at room temperature. Notably, the SBA-15 immobilized Rh(I) catalysts, in which the pore walls provide an additional confinement, showed excellent β-(Z)-selectivity in the hydrosilylation of aliphatic alkynes, too. Also, in the case of 4-aminophenylacetylene, selective formation of the β(Z)-isomer was observed with a neutral SBA-15 supported Rh(III) Cp* NHC complex but not with its homogenous counterpart. These are the first examples of high β(Z)-selectivity in the hydrosilylation of alkynes by confinement generated upon immobilization inside mesoporous silica.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Immobilized Platinum Hydride Species as Catalysts for Olefin Isomerizations and Enyne Cycloisomerizations - Maier, Sarah; Cronin, Steve P.; Vu Dinh, Manh-Anh; Li, Zheng; Dyballa, Michael; Nowakowski, Michał; Bauer, Matthias; Estes, Deven P. (Organometallics)
Platinum hydride species catalyze a number of interesting organic reactions. However, their reactions typically involve the use of high loadings of noble metal and are difficult to recycle, making them somewhat unsustainable. We have synthesized surface-immobilized Pt–H species via oxidative addition of surface OH groups to Pt(PtBu3)2 (1), a rarely used immobilization technique in surface organometallic chemistry. The hydride species thus made were characterized by infrared, magic-angle spinning nuclear magnetic resonance, and X-ray absorption spectroscopies and catalyzed both olefin isomerization and cycloisomerization of a 1,6 enyne (5) with a high selectivity and low Pt loading.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry

Fundamental Characterization, Photophysics and Photocatalysis of a Base Metal Iron(II)‐Cobalt(III) Dyad - Huber-Gedert, Marina; Nowakowski, Michał; Kertmen, Ahmet; Burkhardt, Lukas; Lindner, Natalia; Schoch, Roland; Herbst‐Irmer, Regine; Neuba, Adam; Schmitz, Lennart; Choi, Tae‐Kyu; Kubicki, Jacek; Gawelda, Wojciech; et al. (Chemistry – A European Journal)
Keywords: Photocatalytic Hydrogen Production; Catalysis; Inorganic Chemistry

When Donors Turn into Acceptors: Ground and Excited State Properties of FeII Complexes with Amine-Substituted Tridentate Bis-imidazole-2-ylidene Pyridine Ligands - Vukadinovic, Yannik; Burkhardt, Lukas; Päpcke, Ayla; Miletic, Anabel; Fritsch, Lorena; Altenburger, Björn; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)

N-heterocyclic carbene based iron and ruthenium photosensitizer with amine donors - A systematic study on spectroscopic differences - Vukadinovic, Yannik

Ground- and Excited-State Properties of Iron(II) Complexes Linked to Organic Chromophores - Dierks, Philipp; Päpcke, Ayla; Bokareva, Olga S.; Altenburger, Björn; Reuter, Thomas; Heinze, Katja; Kühn, Oliver; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Key activity descriptors of nickel-iron oxygen evolution electrocatalysts in the presence of alkali metal cations - Görlin, Mikaela; Halldin Stenlid, Joakim; Koroidov, Sergey; Wang, Hsin-Yi; Börner, Mia; Shipilin, Mikhail; Kalinko, Aleksandr; Murzin, Vadim; Safonova, Olga V.; Nachtegaal, Maarten; Uheida, Abdusalam; Dutta, Joydeep; et al. (Nature Communications)
Abstract Efficient oxygen evolution reaction (OER) electrocatalysts are pivotal for sustainable fuel production, where the Ni-Fe oxyhydroxide (OOH) is among the most active catalysts for alkaline OER. Electrolyte alkali metal cations have been shown to modify the activity and reaction intermediates, however, the exact mechanism is at question due to unexplained deviations from the cation size trend. Our X-ray absorption spectroelectrochemical results show that bigger cations shift the Ni 2+/(3+δ)+ redox peak and OER activity to lower potentials (however, with typical discrepancies), following the order CsOH > NaOH ≈ KOH > RbOH > LiOH. Here, we find that the OER activity follows the variations in electrolyte pH rather than a specific cation, which accounts for differences both in basicity of the alkali hydroxides and other contributing anomalies. Our density functional theory-derived reactivity descriptors confirm that cations impose negligible effect on the Lewis acidity of Ni, Fe, and O lattice sites, thus strengthening the conclusions of an indirect pH effect.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Hard X-ray-based techniques for structural investigations of CO2 methanation catalysts prepared by MOF decomposition - Prinz, Nils; Schwensow, Leif; Strübbe, Sven; Jentys, Andreas; Bauer, Matthias; Kleist, Wolfgang; Zobel, Mirijam (Nanoscale)
We investigate the structure-activity correlations of methanation catalysts obtained by thermal decomposition of a Ni-based metal-organic framework, using pair distribution function, X-ray absorption spectroscopy and X-ray diffraction.
Keywords: General Materials Science

Water structure near the surface of Weyl semimetals as catalysts in photocatalytic proton reduction - Gujt, Jure; Zimmer, Peter; Zysk, Frederik; Süß, Vicky; Felser, Claudia; Bauer, Matthias; Kühne, Thomas (Structural Dynamics)
Keywords: Spectroscopy; Condensed Matter Physics; Instrumentation; Radiation

High cycle life all-solid-state fluoride ion battery with La 2 NiO 4+d high voltage cathode - Nowroozi, Mohammad Ali; Wissel, Kerstin; Donzelli, Manuel; Hosseinpourkahvaz, Niloofar; Plana-Ruiz, Sergi; Kolb, Ute; Schoch, Roland; Bauer, Matthias; Malik, Ali Muhammad; Rohrer, Jochen; Ivlev, Sergei; Kraus, Florian; et al. (Communications Materials)
Abstract Fluoride ion batteries (FIBs) are a recent alternative all-solid-state battery technology. However, the FIB systems proposed so far suffer from poor cycling performance. In this work, we report La 2 NiO 4.13 with a Ruddlesden-Popper type structure as an intercalation-based active cathode material in all solid-state FIB with excellent cycling performance. The critical charging conditions to maintain the conductivity of the cell were determined, which seems to be a major obstacle towards improving the cycling stability of FIBs. For optimized operating conditions, a cycle life of about 60 cycles and over 220 cycles for critical cut-off capacities of 50 mAh/g and 30 mAh/g, respectively, could be achieved, with average Coulombic efficiencies between 95 – 99%. Cycling of the cell is a result of fluorination/de-fluorination into and from the La 2 NiO 4+d cathode, and it is revealed that La 2 NiO 4.13 is a multivalent electrode material. Our findings suggest that La 2 NiO 4.13 is a promising high energy cathode for FIBs.
Keywords: Mechanics of Materials; General Materials Science

Intersystem Crossing and Triplet Dynamics in an Iron(II) N-Heterocyclic Carbene Photosensitizer - Zobel, J. Patrick; Bokareva, Olga S.; Zimmer, Peter; Wölper, Christoph; Bauer, Matthias; González, Leticia (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Revealing Hot and Long-Lived Metastable Spin States in the Photoinduced Switching of Solvated Metallogrid Complexes with Femtosecond Optical and X-ray Spectroscopies - Naumova, Maria A.; Kalinko, Aleksandr; Wong, Joanne W. L.; Abdellah, Mohamed; Geng, Huifang; Domenichini, Edoardo; Meng, Jie; Gutierrez, Sol Alvarez; Mante, Pierre-Adrien; Lin, Weihua; Zalden, Peter; Galler, Andreas; et al. (The Journal of Physical Chemistry Letters)
Keywords: General Materials Science; Physical and Theoretical Chemistry

Exploring the light-induced dynamics in solvated metallogrid complexes with femtosecond pulses across the electromagnetic spectrum - Naumova, Maria A.; Kalinko, Aleksandr; Wong, Joanne W. L.; Alvarez Gutierrez, Sol; Meng, Jie; Liang, Mingli; Abdellah, Mohamed; Geng, Huifang; Lin, Weihua; Kubicek, Katharina; Biednov, Mykola; Lima, Frederico; et al. (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Chemical and Morphological Transition of Poly(acrylonitrile)/Poly(vinylidene Fluoride) Blend Nanofibers during Oxidative Stabilization and Incipient Carbonization - Wortmann, Martin; Frese, Natalie; Mamun, Al; Trabelsi, Marah; Keil, Waldemar; Büker, Björn; Javed, Ali; Tiemann, Michael; Moritzer, Elmar; Ehrmann, Andrea; Hütten, Andreas; Schmidt, Claudia; et al. (Nanomaterials)
Thermally stabilized and subsequently carbonized nanofibers are a promising material for many technical applications in fields such as tissue engineering or energy storage. They can be obtained from a variety of different polymer precursors via electrospinning. While some methods have been tested for post-carbonization doping of nanofibers with the desired ingredients, very little is known about carbonization of blend nanofibers from two or more polymeric precursors. In this paper, we report on the preparation, thermal treatment and resulting properties of poly(acrylonitrile) (PAN)/poly(vinylidene fluoride) (PVDF) blend nanofibers produced by wire-based electrospinning of binary polymer solutions. Using a wide variety of spectroscopic, microscopic and thermal characterization methods, the chemical and morphological transition during oxidative stabilization (280 °C) and incipient carbonization (500 °C) was thoroughly investigated. Both PAN and PVDF precursor polymers were detected and analyzed qualitatively and quantitatively during all stages of thermal treatment. Compared to pure PAN nanofibers, the blend nanofibers showed increased fiber diameters, strong reduction of undesired morphological changes during oxidative stabilization and increased conductivity after carbonization.

Humidity-Mediated Anisotropic Proton Conductivity through the 1D Channels of Co-MOF-74 - Javed, Ali; Strauss, Ina; Bunzen, Hana; Caro, Jürgen; Tiemann, Michael (Nanomaterials)
Large Co-MOF-74 crystals of a few hundred micrometers were prepared by solvothermal synthesis, and their structure and morphology were characterized by scanning electron microscopy (SEM), IR, and Raman spectroscopy. The hydrothermal stability of the material up to 60 °C at 93% relative humidity was verified by temperature-dependent XRD. Proton conductivity was studied by impedance spectroscopy, using a single crystal. By varying the relative humidity (70–95%), temperature (21–60 °C), and orientation of the crystal relative to the electrical potential, it was found that proton conduction occurs predominantly through the linear, unidirectional (1D) micropore channels of Co-MOF-74, and that water molecules inside the channels are responsible for the proton mobility by a Grotthuss-type mechanism.

Cellulose Nanocrystal-Templated Tin Dioxide Thin Films for Gas Sensing - Ivanova, Alesja; Frka-Petesic, Bruno; Paul, Andrej; Wagner, Thorsten; Jumabekov, Askhat N.; Vilk, Yury; Weber, Johannes; Schmedt auf der Günne, Jörn; Vignolini, Silvia; Tiemann, Michael; Fattakhova-Rohlfing, Dina; Bein, Thomas (ACS Applied Materials & Interfaces)
Porous tin dioxide is an important low-cost semiconductor applied in electronics, gas sensors, and biosensors. Here, we present a versatile template-assisted synthesis of nanostructured tin dioxide thin films using cellulose nanocrystals (CNCs). We demonstrate that the structural features of CNC-templated tin dioxide films strongly depend on the precursor composition. The precursor properties were studied by using low-temperature nuclear magnetic resonance spectroscopy of tin tetrachloride in solution. We demonstrate that it is possible to optimize the precursor conditions to obtain homogeneous precursor mixtures and therefore highly porous thin films with pore dimensions in the range of 10–20 nm (ABET = 46–64 m2 g–1, measured on powder). Finally, by exploiting the high surface area of the material, we developed a resistive gas sensor based on CNC-templated tin dioxide. The sensor shows high sensitivity to carbon monoxide (CO) in ppm concentrations and low cross-sensitivity to humidity. Most importantly, the sensing kinetics are remarkably fast; both the response to the analyte gas and the signal decay after gas exposure occur within a few seconds, faster than in standard SnO2-based CO sensors. This is attributed to the high gas accessibility of the very thin porous film.

Nanoporous aluminum oxide micropatterns prepared by hydrogel templating - Chen, Zimei; Kuckling, Dirk; Tiemann, Michael (Nanotechnology)
Micropatterned nanoporous aluminum oxide arrays are prepared on silicon wafer substrates by using photopolymerized poly(dimethylacrylamide) hydrogels as porogenic matrices. Hydrogel micropatterns are fabricated by spreading the prepolymer mixture on the substrate, followed by UV photopolymerization through a micropatterned mask. The hydrogel is covalently bonded to the substrate surface. Al2O3 is produced by swelling the hydrogel in a saturated aluminum nitrate solution and subsequent thermal conversion/calcination. As a result, micropatterned porous Al2O3 microdots with heights in µm range and large specific surface areas up to 274 m2 g−1 are obtained. Hence, the hydrogel fulfills a dual templating function, namely micropatterning and nanoporosity generation. The impact of varying the photopolymerization time on the properties of the products is studied. Samples are characterized by light and confocal laser scanning microscopy, scanning electron microscopy, energy-dispersive x-ray spectrometry, and Kr physisorption analysis.

Synthesis of Metal Oxide Inverse Opals from Metal Nitrates by PMMA Colloidal Crystal Templating - Zhang, Xuyang; Weinberger, Christian; Amrehn, Sabrina; Wu, Xia; Tiemann, Michael; Wagner, Thorsten (European Journal of Inorganic Chemistry)
Metal oxide inverse opals are interesting for various applications. To achieve highly ordered inverse opal structures, one important issue during the colloidal crystal templating procedure is to form a stable precursor network before the template loses its structural integrity at high temperature. Using poly(methyl methacrylate), PMMA, colloidal crystal templates, it is essential to consider the physical and chemical changes of the precursors induced by the changes of PMMA during the thermal conversion. For a systematic investigation of this matter, we synthesized a variety of metal oxide inverse opals from the respective metal nitrates, including Cr2O3, Ga2O3, Fe2O3, In2O3, CuO, CeO2, and ZnO, to compare the effect of various modifications of precursors on the structural and optical properties. When the nitrate precursors have a lower thermal stability than the PMMA template, we have modified the metal nitrates by chelating or by polyacrylamide gelation to form more stable precursor networks.

Proton Conduction in a Single Crystal of a Phosphonato‐Sulfonate‐Based Coordination Polymer: Mechanistic Insight - Javed, Ali; Wagner, Thorsten; Wöhlbrandt, Stephan; Stock, Norbert; Tiemann, Michael (ChemPhysChem)
The proton conduction properties of a phosphonato-sulfonate-based coordination polymer are studied by impedance spectroscopy using a single crystal specimen. Two distinct conduction mechanisms are identified. Water-mediated conductance along the crystal surface occurs by mass transport, as evidenced by a high activation energy (0.54 eV). In addition, intrinsic conduction by proton ′hopping′ through the interior of the crystal with a low activation energy (0.31 eV) is observed. This latter conduction is anisotropic with respect to the crystal structure and seems to occur through a channel along the c axis of the orthorhombic crystal. Proton conduction is assumed to be mediated by sulfonate groups and non-coordinating water molecules that are part of the crystal structure.

Functional Nanoporous Materials - Weinberger, Christian; Tiemann, Michael (Nanomaterials)
This Special Issue on “Functional Nanoporous Materials” in the MDPI journal nanomaterials features seven original papers ...

Long- and Short-Term Tensile Strength and Morphology of Joined Beta-Nucleated Polypropylene Parts - Wübbeke, Andrea; Schöppner, Volker; Paul, André; Tiemann, Michael; Austermeier, Laura; Fitze, Marcus; Chen, Mingie; Jakob, Fabian; Heim, Hans-Peter; Wu, Tao; Niendorf, Thomas; Röhricht, Marie-Luise; et al. (SPE ANTEC 2020: The Virtual Edition 5)
This paper presents the results of static short-term and long-term tensile tests for beta-nucleated joined polypropylene samples by the hot plate welding process. In the present study different dimensionless joining displacements are accounted for. The results show that high short-term tensile strength does not directly transfer to high long-term tensile strength. The morphology of the weld seam in the joined samples is examined by means of transmitted and reflected light microscopy. For the dimensionless joining displacements of 0.75 and 0.95, stretched spherulites are obtained. X-Ray diffraction can be used as a tool for qualitative and quantitative analysis and eventually for differentiation of samples of various joining displacements.

Selected Aspects for the Assessment of Laser Transmission Welding - Schöppner, Volker; Wübbeke, Andrea; Schriegel, Fabian; Paul, Andrej; Tiemann, Michael; Geißler, Bastian; Schmidt, Michael; Magnier, Arnaud; Niendorf, Thomas (Joining Plastics)
In diesem Artikel werden das Scherzugverhalten und der morphologische Zustand von konturgeschweißtem Polypropylen (PP) mit einem Massenanteil von 0,2% Ruß untersucht. Dabei zeigen die Ergebnisse ...